Assessment of husbandry practice and egg production performance of indigenous chickens in urban and peri urban area of Guder town, Oromia Region, Ethiopia - Duguma, Chala (Journal of Scientific Agriculture, 2021)
The study was undertaken from May up to July 2020 in Guder town of Oromia regional state, Ethiopia. The aim of the study was to explore husbandry practices and egg production performance of indigenous chicken in the study area. A cross-sectional systematic random survey of 40 households was undertaken by using semi-structured and pre tested questionnaire. Information on management practices, production systems, egg production performances and constraints of indigenous chicken kept in Guder town was generated by semi-structured questionnaire. The primary data collected from house hold survey was processed and analyzed by using a statistical package for social science (SPSS) version 20.0 software. Descriptive statistics such as percentage, mean, ranking, standard deviation, and cross tabulation were used to analyze the data quantitatively. Data gathered through key informant interviews, focus group discussion and personal observation was analyzed qualitatively to strengthen data obtained from the household survey. Due to its small space and lower capital requirement sample household’s ranked chicken as the first important animals kept in the study area. The main purposes of keeping indigenous chicken in the study area were for home consumption followed by generation of income. The most important feed resources of indigenous chicken kept in the study area were feed obtained from scavenging, house hold wastes, the market left over, and industrial by products. Majority of the households accommodated their indigenous chicken in a separate house constructed for the confinement of the chicken. The higher mortality rate of indigenous chicken in the study area was caused by disease and predator. The most commonly happening and economically important disease in the study area was Newcastle. The commonly observed predators in the study area were cat and dog. Health and feed problems were the first and the second constraint of indigenous chicken production in the study area respectively. Therefore area based development involvement could help to increase the productivity of indigenous chicken and thereby improve the income of small holders.